Pushkin and Byron in British Pushkin studies: Strategies of communication and imagological mechanisms - Svetlana B. Koroleva (RUDN Journal of Studies in Literature and Journalism)
The article describes the place and major components of the question of Byron’s influence on Pushkin in British Pushkin studies at the stage of its formation (1910s-1940s). It argues that in the context of ‘turning to Pushkin’ and orientation toward the ‘horizon of the reader’s expectations’, one of the two leading communicative strategies in British books about the Russian poet occurred to be the strategy of combating the stereotype of him as a consistent ‘Russian Byron’. At the same time, starting with M. Baring, British researchers include this issue in the strategy of bringing Pushkin closer to the British reader. The two identified strategies are, to one degree or another, combined in the Byron - Pushkin problem with the principles of historical periodization (historicization of narrative) and aesthetic evaluation, as well as with an imagologically charged cultural approach. The article reveals convergences and divergences in this issue of two key works of the highlighted period - An Outline of Russian Literature (1914) by M. Baring and A History of Russian Literature by D.S. Mirsky (1926). It is argued that Baring declaratively emphasizes Pushkin’s innovation in the re-creation of Byron’s genre forms, the hero and the features of poetics, highlights the depth of ‘Russianness’ of Pushkin’s works and asserts the superiority of the Russian poet over the English one in poetic skill and worldview. Mirsky, relying on the well-known work of V.M. Zhirmunsky and largely following Baring, fights the stereotypical idea of Pushkin’s imitation of Byron from the position of philological accuracy. It has been established in the article that in the context of the Cold War, orientation towards the ‘horizon of the reader’s expectations’ in J. Lavrin’s book Pushkin and Russian Literature (1947) formed the vector for ‘exalting’ Pushkin as a way of ‘justifying’ Russian culture and history. The tangible center of such an imagologically colored rapprochement was Lavrin’s analytical analysis of Pushkin’s polemic with Byron based on the material of his lyrical-heroic poem Poltava.